1971
DOI: 10.1007/bf01877754
|View full text |Cite
|
Sign up to set email alerts
|

The general stationary gravitational vacuum field of cylindrical symmetry

Abstract: The general stationary vacuum gravitational field of cylindrical symmetry as recently found by Davies and Caplan is even static. The possible Petrov types of the Riemann tensor are I, D or O. In spacelike infinity the spacetime becomes necessarily flat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Hence the spacetime is flat inside the shell (R = 0) and the exterior field is static ( B = 0). These conclusions agree with the results of the exact theory [6][7][8], though the general situation is more complicated [6].…”
Section: Introductionsupporting
confidence: 89%
“…Hence the spacetime is flat inside the shell (R = 0) and the exterior field is static ( B = 0). These conclusions agree with the results of the exact theory [6][7][8], though the general situation is more complicated [6].…”
Section: Introductionsupporting
confidence: 89%
“…Recently we have shown [1] (in the following cited as I), that the general stationary cylindrical vacuum field, found by Davies and Caplan [2] is static, whereafter, it is identical with Levi-Civitas general static solution [3]. Hence any stationary (rotating) cylindrical matter distributions generate a static cylindrical vacuum field.…”
Section: Introductionmentioning
confidence: 95%
“…(3.10c) 10 In [46] it was shown that the above solution can be transformed to Kasner's solution [47]. However, the transformation becomes singular in the static limit (given by E → 0 as we will see later) and hence is not suited to our needs.…”
Section: Bulk-brane Systemmentioning
confidence: 99%